Clinical Evaluation and Utilization of Multiple Molecular In Vitro Diagnostic Assays for the Detection of SARS-CoV-2. Issue 2 (28th May 2020) - Cradic, Kendall; Lockhart, Marie; Ozbolt, Patrick; Fatica, Lisa; Landon, Lorie; Lieber, Michael; Yang, David; Swickard, Juanita; Wongchaowart, Nicholas; Fuhrman, Susan; Antonara, Stella
Abstract: Objectives: To evaluate the clinical performance of 3 molecular assays for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Methods: We used 184 nasopharyngeal swab specimens to compare Abbott ID NOW COVID-19 (Abbott ID NOW), DiaSorin Molecular Simplexa COVID-19 Direct (DiaSorin Simplexa), and Roche cobas 6800 SARS-CoV-2 (Roche cobas) assays. In a separate analysis, 3 specimens (nasopharyngeal, oropharyngeal, and nasal) were collected from 182 unique patients presenting to the emergency department with suspicion of coronavirus disease 2019 and were tested utilizing Abbott ID NOW. To further characterize each assay, relative limits of detection were evaluated utilizing positive nasopharyngeal patient samples. Results: The positive percent agreement was 91% (95% confidence interval [CI], 0.76-0.97) for Abbott ID NOW and 100% (95% CI, 0.90-1.00) for DiaSorin Simplexa and Roche cobas. The negative percent agreement was 100% (95% CI, 0.98-1.00) for all 3 assays. All swab types tested with the Abbott assay produced concordant results. Polymerase chain reaction assays had approximately 10 to 100 times lower limits of detection than Abbott ID NOW. Conclusions: Based on these evaluations, a multiplatform testing approach is proposed, depending on patient population and assay sensitivity, to address testing needs during a public health emergency.